PENGARUH KEPEMIMPINAN INSTRUKSIONAL TERHADAP KINERJA PEGAWAI: MOTIVASI SEBAGAI VARIABEL MEDIASI DAN TAMBAHAN PENGHASILAN PEGAWAI (TPP) SEBAGAI VARIABEL MODERASI (Studi pada Pegawai Bagian Umum Sekretariat Daerah Kabupaten Malang) - Adisetyo Yoga Perdana; Nasharuddin Mas; Survival (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to analyze the influence of instructional leadership on employee performance, with motivation as a mediating variable and Employee Additional Income (TPP) as a moderating variable.The population of this research consists of all 64 employees of the General Section of the Regional Secretariat of Malang Regency. Given a population of 64 employees, total sampling was determined as the most appropriate sampling method. In this study, inferential statistical analysis will be at the core of hypothesis testing, utilizing a Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS). SmartPLS version 4 was used to facilitate these hypothesis tests.The results show that instructional leadership has a positive and significant effect on employee performance. Instructional leadership also has a positive and significant effect on motivation. Motivation has a positive and significant effect on employee performance. Employee Additional Income (TPP) has a positive and significant effect on employee performance. Motivation mediates the effect of instructional leadership on employee performance. However, Employee Additional Income (TPP) does not moderate the relationship between instructional leadership and employee performance, nor does it moderate the relationship between motivation and employee performance